The Art Of Persuasion In The Political Arena: The Vital Role Of Rhetoric In Shaping Public Opinion - Santi, Triana; Katimin, Katimin; Samosir, Hasrat Efendi (Program Pascasarjana UIN Sumatera Utara, 2025)
This research aims to analyze in-depth the use of rhetorical persuasion by political actors in the Indonesian political arena and the role of this rhetoric in shaping public opinion amidst a fragmented media landscape and intensifying political polarization. Backgrounded by the dynamic political competition and the transformative digital media landscape, this study identifies gaps in previous research, particularly concerning the unique Indonesian political context and the influence of social media on the effectiveness of rhetoric. Employing a qualitative approach with a descriptive analysis design, data were collected through document analysis, including transcripts of political speeches, social media posts of politicians (Twitter, Instagram, Facebook), online news and opinion articles, and political campaign materials. Data analysis was conducted through content analysis, discourse analysis, and interpretation, grounded in Aristotle's classical rhetoric theory, Entman's framing theory, McCombs and Shaw's agenda-setting theory, and Tajfel and Turner's social identity theory. Triangulation techniques were used to ensure the validity and reliability of the findings. The research results indicate that Indonesian political actors strategically employ a variety of rhetorical techniques encompassing ethos, pathos, and logos, as well as utilizing issue framing, agenda-setting through social media, and social identity mobilization to influence public opinion. The exploitation of echo chambers and social media algorithms was identified as a factor that amplifies rhetorical messages and deepens polarization. This study concludes that the art of rhetorical persuasion plays a crucial role in shaping public opinion in Indonesia, especially within the context of digital media and political polarization, and provides theoretical and practical insights into the dynamics of contemporary political communication.